2020
DOI: 10.1186/s12872-020-01719-3
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial block, P terminal force or fragmented QRS do not predict new-onset atrial fibrillation in patients with severe chronic kidney disease

Abstract: Background The prevalence of left atrial enlargement (LAE) and fragmented QRS (fQRS) diagnosed using ECG criteria in patients with severe chronic kidney disease (CKD) is unknown. Furthermore, there is limited data on predicting new-onset atrial fibrillation (AF) with LAE or fQRS in this patient group. Methods We enrolled 165 consecutive non-dialysis patients with CKD stage 4–5 without prior AF diagnosis between 2013 and 2017 in a prospective follow-up cohort study. LAE was defined as total P-wave duration ≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…IAB was found to be predictive of AF in a sub analysis that excluded obese patients. Another study including only patients with CKD stage IV or V found both aIAB and PTFV1 to not be significant predictors of AF (60).…”
Section: Discussionmentioning
confidence: 94%
“…IAB was found to be predictive of AF in a sub analysis that excluded obese patients. Another study including only patients with CKD stage IV or V found both aIAB and PTFV1 to not be significant predictors of AF (60).…”
Section: Discussionmentioning
confidence: 94%
“…Out of the fifteen studies, thirteen reported that the presence of A-IAB was associated with AF, whilst only two studies failed to demonstrate such an association. The first one included 165 patients with chronic kidney disease (CKD) at stage 4 or 5, while the second one involved 240 healthy Italians aged 25–79 years [ 17 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This association has been demonstrated in several clinical scenarios including heart failure, ischemic heart disease, Takotsubo syndrome, transcatheter aortic valve implantation, cardiac amyloidosis, sleep apnea, cavotricuspid isthmus and pulmonary vein ablation, and following electrical/pharmacological cardioversion [32][33][34][35][36][37][38]. However, the predictive power of IAB appears to be lower in other situations, such as severe chronic kidney disease [39]. IAB is also associated with stroke risk [40] and this association is independent of the presence of AF [41] as could be expected due to the aforementioned fibrotic atriopathy that causes electromechanical dissociation.…”
Section: Af and Strokementioning
confidence: 98%